Pengaruh Posisi Terhadap Kekuatan Baut dan Gaya Geser Ditinjau dari Morfologi Fracture Surface pada Sambungan Plat - Nofriady Handra (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2011)
Bolt extension as link which do not destroy connective by component at process unload tide used many in so many industrial area like at bridge construction, building construction and various appliance of engine tool. Usage of amount 3 (bolt fruit three) at 5 (standard hole five) at one particular extension construction can be seen at tacking on two plate with bevel form at building roof construction. If usage more at one particular construction extension hence will have an in with wide of section, apart between hole at each bolt as well as its esthetics value. Formation arrange situation an bolt extension at one particular construction very having an effect on to failure of extension construction, is in this case done conducted by examination to an extension construction by 3 bolt fruit at 10 position differ from the target of searching optimal position in accepting style shift at bolt extension construction used by bolt is galvanic type have full of thread to. Is later got by tension value shift at each bolt and got by optimal position (strong position) and weak position from 10 existing position in accepting style shift [at] extension construction. Optimal position in this experiments are position 2 and 4. The position not optimal is position 6. Keywords: fracture surface, bolt , optimal position of bolt, deformation.